Seismic performance limit of nuclear power plant piping system with seismic isolation system considering measurement points: Damage index. (December 2021) - Kim, Sung-Wan; Jeon, Bub-Gyu; Hahm, Dae-Gi; Kim, Min-Kyu
Highlights: The damage index can be used to quantitatively express the seismic performance limits of thin-walled steel pipe elbows. Seismic performance limit for the thin-walled steel pipe elbow were presented using the force–displacement and moment-deformation angle relationships. The seismic performance limit was quantitatively defined using a damage index. Abstract: This paper presents the second part of a two-part investigation on the seismic performance limits of nuclear power plant piping systems with seismic isolation systems considering the measurement points and aims to quantitatively express these limits using a damage index based on the dissipated energy. This part of the study focuses on a method to quantitatively express the seismic performance limits needed for seismic fragility evaluations of crossover piping systems connecting structures with and without seismic isolation systems in nuclear power plants. Test specimens for this study were manufactured by welding straight pipes to both ends of a 90° long pipe elbow. The dissipated energy was calculated using the relationship between the moment measured at the center of the pipe elbow and relative deformation angle at each of the straight pipe's measurement points using an imaging system; this was compared to the dissipated energy calculated from the relationship between force and displacement, and a suitable length of the straight pipe for low-cycle fatigue tests was found. Further, a method of applying a weighting factor to the yield points, which are needed to calculate the damage index, are examined; thus, it was confirmed that the damage index can be used to quantitatively express the seismic performance limits of thin-walled steel pipe elbows.